2021
DOI: 10.3390/ijerph19010261
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Wellbeing of Indigenous and Tribal Peoples around the Globe: Ensuring and Promoting Best Practice in Research

Abstract: Indigenous and Tribal peoples account for approximately 6 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…We hope these conversations create space for all researchers, funding agencies and journals to explore options to broaden this position statement beyond the publishing stage so the research process is culturally robust from conception to completion to avoid 'end of pipeline' rhetoric and tokenism. Specifically, Indigenous knowledges, ethics, processes and protocols need to be embedded into all stages of the research process [15], including: � cultivating community owned proposals; � research team recruitment and leadership; � culturally responsive methodologies; � strengthening community capacity; � delivering community focused outcomes; � communicating outcomes with cultural appropriate knowledge exchange medias; and � following up and engaging communities on research impact including impact evaluation approaches established at project outset.…”
Section: Let's Normalize Part Of An Indigenous Nation As Perfectly Va...mentioning
confidence: 99%
“…We hope these conversations create space for all researchers, funding agencies and journals to explore options to broaden this position statement beyond the publishing stage so the research process is culturally robust from conception to completion to avoid 'end of pipeline' rhetoric and tokenism. Specifically, Indigenous knowledges, ethics, processes and protocols need to be embedded into all stages of the research process [15], including: � cultivating community owned proposals; � research team recruitment and leadership; � culturally responsive methodologies; � strengthening community capacity; � delivering community focused outcomes; � communicating outcomes with cultural appropriate knowledge exchange medias; and � following up and engaging communities on research impact including impact evaluation approaches established at project outset.…”
Section: Let's Normalize Part Of An Indigenous Nation As Perfectly Va...mentioning
confidence: 99%
“…As Griffiths et al (2021:3) note, this information 'is not typically reported in academic manuscripts, despite it being central to Indigenous and Tribal peoples' research paradigms, as well as a practical step towards decolonising research'. Initial examinations of the Bharti et al (2015) model indicated that it captured important aspects of the collaboration process identified by Griffiths et al (2021) such as the nature of Aboriginal peoples' engagement (Pillar 1: Interactive Environment); involvement (Pillar 3: Co-production); leadership and research governance considerations (Pillar 5: Management Structure); and whether the work reflected Aboriginal peoples' priorities (Pillar 4: Benefits). As such the model was considered suitable to examine a project bringing together Aboriginal and Western methodologies.…”
Section: A Focus On the Co-creation Processmentioning
confidence: 99%
“…The challenges can be amplified for marginalised groups where there is the very real threat of actually doing harm and perpetuating marginalisation through research. This article seeks to impact the practice of marketing researchers by examining how Bharti et al’s (2015) model of value co-creation can help research teams to work together, in culturally sensitive and safe ways, to privilege the voices of marginalised groups and maximise value for all stakeholders (Griffiths et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It was in 2007 that the United Nations Declaration on the Rights of Indigenous peoples, Article 2 stated ‘the right to be free from any kind of discrimination, in the exercise of their rights, in particular that based on their indigenous origin or identity’ 20 . The ICIRAS would be a lever for embedding the rights of Indigenous peoples into academic publishing governance, as aligned to the movement for embedding human rights in research with Indigenous and Tribal peoples 21 …”
Section: Why a Standard?mentioning
confidence: 99%